Successful therapy of a newborn with Stenotrophomonas maltophilia nosocomial pneumonia with cefiderocol - Trauth, Janina; Schuler, Rahel; Waitz, Markus; Ehrhardt, Harald; Fritzenwanker, Moritz; Herold, Susanne; Justus Liebig University Giessen (My University, 2024)
Cefiderocol is a new siderophore-beta-lactam antibiotic used for the treatment of severe multidrug-resistant infections like sepsis, hospital-acquired and ventilator-associated pneumonia in adults, but there are only single reports on its use in the neonatal population. We describe the successful cefiderocol treatment of a newborn with pneumogenic sepsis due to Stenotrophomonas maltophilia.
Keywords: ddc:610